Linguistics Deviations in Kipling's Selected Poems - Suzanna Widjayanti (Ethical Lingua: Journal of Language Teaching and Literature, 2014)
This study investigated Kipling's way of handling poetic language on his five selected poem (Fuzzy Wuzzy, Gunga Din, Mandalay, The White Burden Man, and If), which regarded as purposively samples from forty of the available familiar poems collection and relies on three main language levels: realization, form, and semantics Leech breaks down.